1991
DOI: 10.1159/000216247
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Leukocyte Elastase Concentration in Plasma and Serum by a Simple Method Using a Specific Synthetic Substrate

Abstract: The concentration of leukocyte elastase (ELP) in plasma and serum was determined by an amidolysis method using a specific synthetic substrate for ELP, Suc-Ala-Tyr-Leu-Val-pNA. Results were compared with those using ELISA. ELP levels in plasma from healthy donors were similar to those determined by ELISA; however, the levels in serum were lower than those determined by ELISA. Correlation coefficients of ELP levels in plasma and serum as measured by the two methods were 0.75 (amidolysis) and 0.90 (ELISA). On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…No mutations were identified in at least 30 healthy controls, but 50% frequency in polymorphisms was detected in healthy individuals. These results are compatible with those published previously, showing that a high level of ELA2 is caused in AML (14)(15)(22)(23)(24). The pathogenicity of mutations in ELA2 remains a mystery.…”
Section: Discussionsupporting
confidence: 93%
“…No mutations were identified in at least 30 healthy controls, but 50% frequency in polymorphisms was detected in healthy individuals. These results are compatible with those published previously, showing that a high level of ELA2 is caused in AML (14)(15)(22)(23)(24). The pathogenicity of mutations in ELA2 remains a mystery.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, others and we began to identify the factors and mechanisms that control the emigration of normal cells from the BM into the circulation. The finding that elastase, among other proteolytic enzymes such as cathepsin G and MMPs, participates in the process of G-CSF-induced mobilization of normal stem cells, progenitors, and maturing cells 29,30 led us to hypothesize that the abnormally high levels of elastase in AML patients' plasma 17,19 may facilitate the cells' egress into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Previous studies reported high levels of intracellular elastase activity and secretion of elastase protein by AML cells. [17][18][19] Evidence recently emerged that elastase has a major role in the development of myeloid leukemias. Elastase produced by chronic myelogenous leukemia (CML) neutrophils preferentially suppresses normal hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…Normally serum neutrophil elastase levels are in the order of 200 ng/mL, but much of it is complexed with serpins and therefore is inactive. However, elastase levels correlate directly with the number of peripheral blood neutrophils, 18 and 10 6 neutrophils can release up to 2 g/mL elastase. 19 Furthermore, changes in elastase accompany the administration of G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…18,29,30 The question arises whether an inhibitory effect of elastase on normal granulopoiesis contributes to the dominance of a G-CSF-independent leukemic clone or, alternatively, whether elastase release by leukemic cells could contribute to the maturation arrest of a G-CSF-sensitive leukemic blast cell.…”
Section: Discussionmentioning
confidence: 99%